LITERATURE STUDIES: BLENDED LEARNING ASSISTED BY EDMODO TO INCREASE STUDENT INDEPENDENCE AND LEARNING OUTCOMES - Elvina Irawati Sihite (ISER (Indonesian Science Education Research), 2021)
The purpose of this research is to elaborate a number of thoughts and concepts that believe inthe effect of applying Edmodo-assisted blended learning to improve student independence andlearning outcomes. The research method used is literature study by collecting literature sourcedfrom books, journals and other scientific sources related to Edmodo-assisted blended learning,independent learning and student learning outcomes. Based on the results of the study, blendedlearning was carried out by combining various methods of delivering learning with the help ofonline learning media, namely face-to-face and the use of e-learning. Edmodo facilitatesteachers and students to be able to communicate, collaborate and carry out the learning process,teachers can provide learning content, and students can conduct discussions and collectassignments or homework anytime and anywhere. There are seven indicators of learningindependence, namely: self-confidence, able to work alone, able to make decisions, beresponsible, have a desire to compete, be disciplined and active in learning. Learning outcomesare divided into three domains, namely cognitive, affective, and psychomotor. The results ofthe study concluded that the use of Edmodo-assisted blended learning could increase students'independence and learning outcomes. disciplined and active in learning. Learning outcomes aredivided into three domains, namely cognitive, affective, and psychomotor. The results of thestudy concluded that the use of Edmodo-assisted blended learning could increase students'independence and learning outcomes. disciplined and active in learning. Learning outcomes aredivided into three domains, namely cognitive, affective, and psychomotor. The results of thestudy concluded that the use of Edmodo-assisted blended learning could increase students'independence and learning outcomes.